Analysis on the Development of Professional Literacy of University Libraries in the Ubiquitous Knowledge Environment - WANG Yang, LIU Jiandong, YAN Hongzhong, XIA Qing (Nongye tushu qingbao xuebao, 2020)
[Purpose/Significance] in order to better adapt to the significant changes of knowledge environment in the era of mobile Internet, the professional quality of university librarians will be further developed in an all-round way in the new business environment. [Method/Process] by exploring the ubiquitous characteristics of the knowledge environment of University Library in the era of mobile Internet, this paper analyzes the development and changes of equipment literacy, information literacy and data literacy in the process of reader service generalization of university library. [Results/Conclusions] this paper attempts to put forward the strategies of improving the professional quality of university library, which can provide reference for the construction of the staff team of university library.